Paraffin Granuloma Associated with Buried Glans Penis-Induced Sexual and Voiding Dysfunction - Chon, Wonhee; Koo, Ja Yun; Park, Min Jung; Choi, Kyung-Un; Park, Hyun Jun; Park, Nam Cheol (The world journal of men's health, 2017)
A paraffinoma is a type of inflammatory lipogranuloma that develops after the injection of an artificial mineral oil, such as paraffin or silicon, into the foreskin or the subcutaneous tissue of the penis for the purpose of penis enlargement, cosmetics, or prosthesis. The authors experienced a case of macro-paraffinoma associated with sexual dysfunction, voiding dysfunction, and pain caused by a buried glans penis after a paraffin injection for penis enlargement that had been performed 35 years previously. Herein, this case is presented with a literature review.